THE IMPORTANCE-PERFORMANCE ANALYSIS OF STORE ATMOSPHERE AT MATAHARI DEPARTMENT STORE MANADO TOWN SQUARE - Kaunang, Milenia C.; Tumbuan, Willem J.F.A.; Gunawan, Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
The modern retail business that continues to grow in Indonesia is one of the most promising businesses in the market. Every company always tries to win the competition by trying to achieve the goal of creating and retaining customers. The competition between retail businesses grow fast and very tight currently. For some people shopping is a fun activity to do, shopping is not just buying and selling activity. In contrast to a few years ago, now the shopping activity not only as a routine activity to fulfill and buy goods, but sometimes as entertainment to eliminate boredom. The purpose of this research is to analyse the importance and performance of store atmosphere in Matahari Department Store Manado Town Square. Researchers conducted this research through quantitative methods by using the Importance-Performance Analysis (IPA) approach as an analytical tool. To achieve this goal, the researchers distributed questionnaires and the sample used was 100 respondents with two main samples, namely Generation Y and Z who had visited Matahari Department Store. The result of this study indicate that the indicator of Store Atmosphere which are Store Exterior, General Interior and Interior Display are located in Quadrant 2 means that these indicator achieves high performance to the customer. While the indicator Store Layout in Quadrant 3.Â Keywords: store atmosphere, importance-performance analysis